Cervico-thoracic or lumbar sympathectomy for neuropathic pain and complex regional pain syndrome. - Straube, S; Derry, S; Moore, R; McQuay, H (2010)
BACKGROUND: This review is an update on 'Sympathectomy for neuropathic pain' originally published in Issue 2, 2003. The concept that many neuropathic pain syndromes (traditionally this definition would include complex regional pain syndromes (CRPS)) are "sympathetically maintained pains" has historically led to treatments that interrupt the sympathetic nervous system. Chemical sympathectomies use alcohol or phenol injections to destroy ganglia of the sympathetic chain, while surgical ablation is performed by open removal or electrocoagulation of the sympathetic chain, or minimally invasive procedures using thermal or laser interruption. OBJECTIVES: To review the evidence from randomised, double blind, controlled trials on the efficacy and safety of chemical and surgical sympathectomy for neuropathic pain. Sympathectomy could be compared with placebo (sham) or other active treatment. SEARCH STRATEGY: We searched MEDLINE, EMBASE and The Cochrane Library to May 2010. We screened references in the retrieved articles and literature reviews, and contacted experts in the field of neuropathic pain. SELECTION CRITERIA: Randomised, double blind, placebo or active controlled studies assessing the effects of sympathectomy for neuropathic pain and CRPS. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trial quality and validity, and extracted data. No pooled analysis of data was possible. MAIN RESULTS: Only one study satisfied our inclusion criteria, comparing percutaneous radiofrequency thermal lumbar sympathectomy with lumbar sympathetic neurolysis using phenol in 20 participants with CRPS. There was no comparison of sympathectomy versus sham or placebo. No dichotomous pain outcomes were reported. Average baseline scores of 8-9/10 on several pain scales fell to about 4/10 initially (1 day) and remained at 3-5/10 over four months. There were no significant differences between groups, except for "unpleasant sensation", which was higher with radiofrequency ablation. One participant in the phenol group experienced postsympathectomy neuralgia, while two in the radiofrequency group and one in the phenol group complained of paresthaesia during needle positioning. All participants had soreness at the injection site. AUTHORS' CONCLUSIONS: The practice of surgical and chemical sympathectomy for neuropathic pain and CRPS is based on very little high quality evidence. Sympathectomy should be used cautiously in clinical practice, in carefully selected patients, and probably only after failure of other treatment options.